The effects of endogenous firm exit on business cycle dynamics and optimal fiscal policy - Lauri Vilmi (Sveriges Riksbank, 2011)
We explore the implications of endogenous firm entry and exit for business cycle dynamics and optimal fiscal policy. We first show that when the firm exit rate is endogenous, negative technology shocks lead to reductions in the number of firms. Technology shocks therefore have additional effects on household welfare relative to an economy with only endogenous entry. Second, endogenous firm exit creates a new channel for monetary policy when debt contracts are written in nominal terms, as monetary shocks affect the rate of firm defaults. Monetary shocks therefore have real effects also when prices and wages are flexible. Third, we show that endogenous firm exit creates a new role for fiscal policy to increase efficiency and welfare by subsidizing firms and decreasing the number of defaults. Finally, we demonstrate that endogenous firm exit implies that non-persistent shocks to technology and money supply have persistent effects on labor productivity. This has implications for the estimated persistence of technology shocks.
Keywords: E32; E52; 330; firm defaults; money supply shock; labor productivity; Konjunktur; Insolvenz; Geldmenge; Schock; Arbeitsproduktivität; Theorie